2018
DOI: 10.1002/brb3.1119
|View full text |Cite
|
Sign up to set email alerts
|

Are people with amyotrophic lateral sclerosis (ALS) particularly nice? An international online case–control study of the Big Five personality factors

Abstract: BackgroundMany people with ALS have been suggested to have a “nice” personality, but most ALS personality studies to date have had limited numbers of participants and have not taken into account personality differences between genders. We used Big Five Inventory data obtained from an online questionnaire looking for risk factors for ALS to investigate personality traits in large numbers of people with ALS and controls.MethodsA total of 741 questionnaire respondents aged 40 years and over indicated the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This is the key and novel finding of the present study. While only one previous study had investigated ALS patients’ premorbid personality, finding higher levels of Extraversion, Agreeableness, and Conscientiousness in ALS patients relative to healthy controls ( Parkin Kullmann et al, 2018 ), no studies explored premorbid personality as a driving factor for phenotypic variability. Although in line with these results, our study shows that it is the FTD group, rather than the ALS, which deviates from the reference sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the key and novel finding of the present study. While only one previous study had investigated ALS patients’ premorbid personality, finding higher levels of Extraversion, Agreeableness, and Conscientiousness in ALS patients relative to healthy controls ( Parkin Kullmann et al, 2018 ), no studies explored premorbid personality as a driving factor for phenotypic variability. Although in line with these results, our study shows that it is the FTD group, rather than the ALS, which deviates from the reference sample.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologists caring for patients with ALS have variably described them as “pleasant,” “friendly”, “sympathetic”, “nice” ( Wilbourn and Mitsumoto, 1998 ; Borasio and Miller, 2001 ; Mehl et al, 2017 ), emphasizing their active involvement in medical care and their remarkable resilience in coping with their disease. Indeed, since the 1970s several authors have described the peculiar personality profile of patients with ALS in comparison with either healthy controls or patients with other chronic, progressive non-neurodegenerative conditions, suggesting a possible relationship with the etiological factors of the disease ( Brown and Mueller, 1970 ; Peters et al, 1978 ; Grossman et al, 2006 ; Mehl et al, 2017 ; Parkin Kullmann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…showed that ALS patients are more agreeable and less neurotic than controls. 4 We should consider whether ALS patients are less depressed because other people are nicer to them. ALS's status as a rare tragedy rather than a chronic disease protects patients from caregiver compassion fatigue, as does the fact that ALS patients are not prone to the psychosis and impulsivity of Alzheimer disease and late Parkinson disease.…”
Section: Dr Alice Flahertymentioning
confidence: 99%
“…However, limited knowledge exists regarding coping traits according to personality traits in ALS, apart from an elevated anxiety trait being associated with decreased quality of life (QoL) (Siciliano et al, 2019 ). The specific personality traits of patients with ALS suggest a strong desire to excel in tasks and a high aim for achievement, compared to healthy controls (Parkin Kullmann et al, 2018 ). However, the extent to which coping traits affect the wellbeing of patients with ALS remains extensively unexplored, prompting us to address this gap.…”
Section: Introductionmentioning
confidence: 99%